2003
DOI: 10.1097/01.phm.0000064730.54787.f5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Unilateral Middle Cerebral Artery Infarcts on Voluntary Cough and the Laryngeal Cough Reflex

Abstract: VC is of limited use in screening subjects for aspiration pneumonia risk. A normal laryngeal cough reflex indicated a neurologically protected airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…When a cough sequence is reflexively triggered, it is usually composed of a mixture of CRs and LERs (Stephens, Addington, & Widdicombe, 2003;Widdicombe & Fontana, 2006). It is difficult to distinguish a CR from an LER in a cough sequence without physiological measures, such as airflow or pressure.…”
Section: Differences Between Reflexive and Voluntary Coughingmentioning
confidence: 99%
See 2 more Smart Citations
“…When a cough sequence is reflexively triggered, it is usually composed of a mixture of CRs and LERs (Stephens, Addington, & Widdicombe, 2003;Widdicombe & Fontana, 2006). It is difficult to distinguish a CR from an LER in a cough sequence without physiological measures, such as airflow or pressure.…”
Section: Differences Between Reflexive and Voluntary Coughingmentioning
confidence: 99%
“…For example, a study that investigated VC and RC in patients following stroke found that they were independent of each other and that VC was impaired in 79% of right-handed patients who had suffered acute left-sided middle cerebral artery (MCA) infarcts but CR remained unimpaired and no patients developed aspiration pneumonia (Stephens et al, 2003). A similar study investigating VC and RC in stroke patients found that 10% of patients had a weak or absent CR, whereas 20% of patients had an abnormal VC (Addington, Stephens, & Gilliland, 1999).…”
Section: Differences Between Reflexive and Voluntary Coughingmentioning
confidence: 99%
See 1 more Smart Citation
“…A volitional cough is cortically mediated and can be initiated with or without laryngeal sensations or spoken requests. 49 Cough can also be suppressed volitionally. Conversely, a reflexive cough, i.e., "laryngeal cough reflex," is a brainstem mediated reflex triggered by sensations in the larynx, e.g., aspiration of food or liquid.…”
mentioning
confidence: 99%
“…Conversely, a reflexive cough, i.e., "laryngeal cough reflex," is a brainstem mediated reflex triggered by sensations in the larynx, e.g., aspiration of food or liquid. 49 Finally, in contrast to the reflexive cough, the term "expiration reflex" refers to reflexive, forced expiration triggered by mechanical or chemical irritation of the vocal folds that occurs without a preceding inspiration. 50 Different patterns of motor activation of respiratory muscles have been observed in volitional versus reflexive cough.…”
mentioning
confidence: 99%